Strategi Creative Branding Hijack Sandals untuk Meningkatkan Brand Image - Ilham Akbar Zam Zamy; Dadi Ahmadi (UPT Publikasi Ilmiah Unisba, 2023)
Abstract.Hijack Sandals is a fashion brand that was born in Bandung in 2010 which until now is still very consistent in selling products that focus on footwear, namely sandals. They were born and appeared in that year because of the concern of the people around them, who made the shoes very comfortable. In fact, the climate in Indonesia is suitable for wearing sandals. Hijack Sandals has dozens of products filled with various kinds of sandals with different motifs and colors. This research is entitled